Critical Analysis of the Role of Management Information Systems in Optimizing Strategic Decision Making - Daud, Ade Apriyanto; Yasani, Siti Marwa; Bohar, Adelia; Latif, Refka; Abdul, Habib (PT. Riset Press International, 2024)
This journal provides a critical analysis of the role of management information systems (SIM) in optimizing strategic decision making in the current business environment. By exploring related literature and relevant case studies, the authors highlight the importance of SIM integration in the strategic decision-making process. This article highlights the challenges organizations face in effectively implementing SIM as well as the opportunities that exist to improve performance through the use of advanced information technology. This analysis not only provides deep insight into the contribution of SIM to strategic decision making, but also identifies areas where improvements can be made to increase the efficiency and effectiveness of the system. In conclusion, this article emphasizes the importance of SIM as a strategic tool that not only facilitates better decision making, but also provides a competitive advantage to organizations in today's digital era.